2015
DOI: 10.1097/mcp.0000000000000174
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of breathlessness associated with pleural effusions

Abstract: Purpose of reviewPleural effusions have a major impact on the cardiorespiratory system. This article reviews the pathophysiological effects of pleural effusions and pleural drainage, their relationship with breathlessness, and highlights key knowledge gaps.Recent findingsThe basis for breathlessness in pleural effusions and relief following thoracentesis is not well understood. Many existing studies on the pathophysiology of breathlessness in pleural effusions are limited by small sample sizes, heterogeneous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 40 publications
2
72
0
13
Order By: Relevance
“…Isolates from two previously described 2013 cases [1] possessed the same sequence types, supporting the hypothesis of a common source of infection.…”
Section: Resultssupporting
confidence: 62%
“…Isolates from two previously described 2013 cases [1] possessed the same sequence types, supporting the hypothesis of a common source of infection.…”
Section: Resultssupporting
confidence: 62%
“…In the Australasian Malignant PLeural Effusion trial‐2, patients with NEL could develop autopleurodesis especially if drained daily via an indwelling pleural catheter (IPC). Clinicians must also discard the old belief that patients with NEL will not derive symptom benefits from fluid drainage (reviewed elsewhere) …”
mentioning
confidence: 99%
“…Clinicians must also discard the old belief that patients with NEL will not derive symptom benefits from fluid drainage (reviewed elsewhere). 8 How should clinicians approach NEL knowing it may require years, if not decades, for research studies to provide a full picture of how best to define, assess and employ NEL for selecting patients for pleurodesis? Research in MPE care has been progressing rapidly in the past decade and the latest finding raises the possibility of bypassing the need of defining NEL.…”
mentioning
confidence: 99%
“…However, the pathophysiology behind MPE-related breathlessness is poorly understood. 96 Not surprisingly, recent studies found that a sizeable number (15-27%) of patients had no symptomatic improvement after therapeutic drainage. Understanding the mechanism of MPE-related breathlessness is critical to aid patient selection for pleural interventions.…”
Section: Future Directionsmentioning
confidence: 98%